Machiavelli : His Life and Times - Lee, Alexander (London Picador, 2020)
A comprehensive, authoritative and highly original portrait of one of history's most unjustly infamous characters.
Include Color Illustrations, Maps and Index
Keywords: Political scientists -- Machiavelli, Niccolò, 1469-1527